Biological physics to uncover cell signaling - Ponce Dawson, Silvina (Biophysical reviews, 2025)
In this report, I describe some of the subjects and problems that we have addressed over the last 25 years in the area of cell signaling using the tools of biological physics. The report covers part of our work on intracellular Ca 2 + signals, pattern formation, transport of messengers in the interior of cells, quantification of biophysical parameters from experiments, and information transmission. The description includes both our modeling and experimental work highlighting how the tools of physics can give useful insights into the workings of biological systems.